Impact of firm characteristics and ownership structure on firm efficiency: evidence from non-financial firms of Pakistan - Shafaat Muhammad Habib; Haroon Hussain; Mamdouh Abdulaziz Saleh Al-Faryan; Rana Yassir Hussain (Cogent Economics & Finance)
This study aims to examine the impact of firm characteristics and ownership structure on the firm efficiency of listed non-financial firms in Pakistan from 2012 to 2017. Firm characteristics include market capitalization, cash holdings, book-to-market ratio and negative book-to-market ratio and ownership structure includes insider ownership, institutional ownership and concentration ownership while controlling for firm size, profitability, leverage and age. Data related to firm efficiency, cash holdings, book-to-market ratio and negative book-to-market ratio was collected from Financial Statement Analysis published by SBP whereas data related to market capitalization and ownership structure (insider ownership, institutional ownership and concentration ownership) was collected from business recorder and published annual reports respectively. At first stage the firm efficiency is reported by using DEA CRS approach and results show that the year 2014 was the best year because 24% firms were efficient and 2015 was the worst because only 18% firms were efficient. The results also show that textile, sugar, food, manufacturing, chemical & pharmaceuticals, cement, motor vehicle, information communication & transportation are the poor performing sectors of Pakistan. This inefficiency might be due to the inefficient use of resources as agency theory advocates. Then at second stage, the correlation and variance inflation factor did not show any multicollinearity. Tobit model is used to find the regression results. The regression results show that market capitalization, cash holdings and concentration ownership positively and significantly influence the firm efficiency. Negative book-to-market ratio, insider ownership and institutional ownership negatively and significantly influence the firm efficiency whereas the book-to-market ratio is insignificant with the firm efficiency. It might be due to the self-interest by the insider and institutional ownership. This study is also helpful for the investors. They can choose the efficient firm for investment and to avoid the inefficient firms to stay away from the losses.